Application of Communication Principles in the Public Relations Strategy of Dp3a City of Bogor in Information Dissemination on Instagram - Akromah, Rahillatul; Dharmawan, Leonard; Mulyawaty, Siska (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This research discusses the Implementation of Communication Principles in the Public Relations Strategy of DP3A Bogor City in Disseminating Information on Instagram. The study aims to explain how communication principles are applied in DP3A’s public relations strategy and to identify the challenges faced in disseminating information through Instagram. The findings show that the DP3A Public Relations team implements the principles of communication based on the Theory of Strategic Communication, which include credibility, context, content, clarity, continuity and consistency, channel, and audience capability. These principles are reflected through various communication strategies such as creating informative and interactive content (reels, feeds, stories), utilizing Instagram features (direct messages, comments, story games), and managing audience engagement based on demographic and behavioral analytics. DP3A’s PR also maintains consistency through scheduled campaigns addressing women’s and children’s issues. Overall, the implementation of strategic communication principles strengthens the effectiveness of information dissemination and supports DP3A’s goal of building a positive public image through digital platforms